Sensory quality and stability of ubi (Dioscorea alata Linn.) peel anthocyanin as a food colorant - Paredes, Ma. Dulce C.; Del Valle, Mercedita (1979.)
The anthocyanin pigment of ubi (Dioscorea alata) peels was extracted with acidified ethanol (0.1% HCL in absolute ethanol), vacuum filtered, and concentrated in a vacuum oven. The dark violet extract has a pH of 3.6. The extract exhibits a violet color at pH 4.0 and has a maximum peak of absorption at 580 nm and a smaller peak at 455 nm. The extract exhibits a red color at pH 3.0 and has a maximum peak of absorption at 560 nm and a smaller peak at 455 nm. The anthocyanin extract was used as a food colorant in a beverage. The beverage was stored under different conditions of pH, temperature, and light. The color stability of the beverage was determined by spectrophotometric reading of the samples every 14 days for a period of 70 days. Statistical analysis of the absorbance readings during the storage study showed that there is a significant difference between the individual effects of pH, temperature, light and days. The beverage adjusted to pH was found to be more stable than the beverage with pH 4.0 Both beverages were more stable at refrigerated temperature (55±5°F) than at room temperature (83±5°F). The effect of light was not clearly defined since the amber bottles and clear vials used to approximate the effect of exposure to light was not of uniform sizes, thus allowing more oxidative degradation in some of the samples. After the 70 days storage period, no browning was observed in all the samples. A preference test was done to determine the color acceptability of the beverage colored with ubi anthocyanin as compared to a commercial beverage. The results of the preference test showed that the color of the red and violet beverages with added anthocyanin was comparable to the color of commercial beverages. A duo-trio test was conducted to determine whether the addition of anthocyanin pigment has any adverse effects on the taste of the beverage. The results showed that 0.1% level of significance, the beverage colored with ubi anthocyanin is significantly different from the beverage colored with synthetic food color. The beverage with anthocyanin had a more sour taste but was not unpleasant.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Coloring matter in food